Woody plant species composition, structure, and regeneration status of ruruki forest of Liban Jawi District, West Shewa Zone, Oromia Regional State, Ethiopia - Bayissa Belay; Tena Regasa; Siraj Mammo (BMC Ecology and Evolution)
Abstract The study was conducted to assess the woody plant species composition, population structure, and regeneration status of Ruruki Forest. A total of 30 sample plots, each 20 m × 20 m, were established using a systematic sampling method. A sub-plot of 5 m × 5 m was used to count saplings and seedlings. To describe the vegetation structure of the study forest we computed DBH and height size frequency distributions of individuals and species importance value indexes (IVI).A total of 70 woody species which categorized into 64 genera, and 45 families were identified of which 57.14% were trees, while shrubs and lianas cover37.14%and5.7%, respectively. The total density of woody species recorded was 868.33 individuals / ha. The highest IVI index was recorded for Syzygium guineense species, indicating the species is ecologically important. The results of height showed that there was a greater predominance of small-sized individuals of woody species than large-sized woody species for the study forest. The general pattern of the DBH class distribution of the forest showed an irregular distribution, which implies there was some selective cutting of individual woody species for different purposes. The overall regeneration status of the forest was found to be fair. Generally, the result obtained from this study shows that there is disturbances and selective cutting of trees in the forest. Hence, there is a need for full participation in sustainable forest management to control selective cutting and to apply the best forest management practices, such as reforestation and afforestation.